Effect of Freeze-Dried and Oven-Dried Cilembu Sweet Potato Flour on the Antioxidant Activity of Chicken Meatballs. - Azchar Prianka Piawan Putra; Muhammad Mar'ie Sirajuddin; Hotlan Malik; Muhammad Husein; Riskayanti Riskayanti; Rizki Prasetya; Stefani Fitri Haryati; Fitri Armianti Arief; Juni Claudia Dami; Ditasari Amalia; Alvin Masruri (Bantara Journal of Animal Science, 2026)
This study evaluated the effect of different dehydration methods, specifically oven drying (60°C) and freeze-drying (-20°C to 65°C), on the antioxidant activity of Cilembu sweet potato (Ipomoea batatas L. Lam) flour and its functional application in chicken meatballs. The antioxidant capacity was measured using the DPPH radical scavenging assay, with results showing that freeze-drying significantly preserved higher levels of bioactive compounds compared to thermal evaporation. Freeze-dried tuber flour reached a radical scavenging activity of 55.74 mg/ml, and when applied to meatballs as a 15% substitute for tapioca flour, it exhibited a superior antioxidant activity of 41.7%. This value was significantly higher (P<0.01) than the oven-dried treatment (28.85%) and the control group (13.22%). The enhanced retention of antioxidants in freeze-drying is attributed to the sublimation process, which minimizes the oxidation and thermal degradation of heat-sensitive molecules such as beta-carotene and phenolic compounds inherently found in Cilembu sweet potatoes. In conclusion, freeze-drying is the more effective processing method for maintaining the functional integrity of local Indonesian tubers, providing a high-quality ingredient for the development of standardized functional foods.